Electronic Waste : Recycling and Reprocessing for a Sustainable Future - Holuszko, M. E.; Kumar, Amit; Espinosa, Denise C. R. (Wiley, 2021)
Discover the latest technologies in the pursuit of zero-waste solutions in the electronics industry In Electronic Waste: Recycling and Reprocessing for a Sustainable Future, a team of expert sustainability researchers delivers a collection of resources that thoroughly examine methods for extracting value from electronic waste while aiming for a zero-waste scenario in industrial production. The book discusses the manufacturing and use of materials in electronic devices while presenting an overview of separation methods for industrial materials. Readers will also benefit from a global overview of various national and international regulations related to the topic of electronic and electrical waste. A must-read resource for scientists and engineers working in the production and development of electronic devices, the authors provide comprehensive overviews of the benefits of achieving a zero-waste solution in electronic and electrical waste, as well as the risks posed by incorrectly disposed of electronic waste. Readers will enjoy: An introduction to electronic waste, including the opportunities presented by zero-waste technologies and solutions Explorations of e-waste management and practices in developed and developing countries and e-waste transboundary movement regulations in a variety of jurisdictions Practical discussions of approaches for estimating e-waste generation and the materials used in electronic equipment and manufacturing perspectives In-depth treatments of various recycling technologies, including physical separation, pyrometallurgy, hydrometallurgy, and biohydrometallurgy Perfect for materials scientists, electronic engineers, and metal processing professionals, Electronic Waste: Recycling and Reprocessing for a Sustainable Future will also earn a place in the libraries of industrial chemists and professionals working in organizations that use large amounts of chemicals or produce electronic waste.